Analysis of Carbon Emission Mitigation Potential from Solid Waste Management at Campus Environment - Vivin Setiani; Ulvi Priastuti; Ahmad Erlan Afiuddin; Mar’atus Sholihah; Denny Dermawan; Mirna Apriani; Dewi Kurniasih; Agus Khumaidi; Aulia Della Cornellia; Lina Indawati; Sekarsari Wibowo (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2026)
Greenhouse gas emissions from waste management contribute to climate change, including in higher education institutions. This study aimed to evaluate the potential for carbon emission mitigation from waste management at the Politeknik Perkapalan Negeri Surabaya campus through organic waste composting and inorganic waste recycling using a waste bank system. The application of solid waste generation measurement was combined with the Intergovernmental Panel Climate Change guidelines and SNI 3964:2025. A descriptive quantitative approach was employed, utilizing primary data on solid waste characteristics from selected campus buildings. Baseline emission estimates and mitigation scenarios were used, assuming partial implementation of the 3R program: organic waste composting and recycling. The results indicate that the waste management sector produces approximately 5.44 tons of CO₂ per year, and the proposed emission reductions could reduce emissions by approximately 63%. The findings of this study indicate that integrated waste management has significant potential for reducing carbon emissions and supporting the development of low-carbon campuses aligned with Sustainable Development Goals 12 and 13, despite the methodological limitations related to the assumptions of emission factors and the level of implementation